Brand Image Indicator on Vivo Smartphone Purchasing Decisions in Pamulang University Students, Faculty of Economics and Business, Management Study Program - Rida Septi Yani; Imelda Bella Treysha; Avantie Sukarsa (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to find out and analyze how big the role of brand image is in purchasing decisions for Vivo smartphone products. The method used in this study is a quantitative method, carried out online via the Google form using a structured questionnaire. A total of 100 samples were recruited using a purposive sampling method. The sample used as a respondent was Pamulang University students in the Faculty of Economics and Business Management Study Program who had purchased a Vivo brand smartphone in the last 5 years. This study used the statistical tool SPSS version 25 (Statistical Product and Service Solution) to process the data. The results showed that brand image and product quality had a significant positive effect on purchasing decisions.